Effect of Fe2O3 Addition and Sintering Temperature on mechanical Properties and Translucence of Zirconia Dental Ceramics with Different Y2O3 Content - Alves,Manuel Fellipe R. P. (2021)
The influence of Fe2O3 additions on the microstructure, mechanical properties and translucence of zirconia with 3 mol-% or 5 mol-% Y2O3 was evaluated. Samples were pressed with different thickness and sintered at 1475, 1500, 1550 and 1600°C for 2 h. Density, phases, microstructure, roughness, strength and translucency were analyzed. All samples showed densification greater than 99%. After sintering at 1600°C, the phase analysis revealed only tetragonal ZrO2 in samples with 3% Y2O3, while in samples with 5% Y2O3 the cubic ZrO2 phase was identified. Significant increase in the grain size was noted, when increasing the Y2O3 content from 3% to 5% from 0.8 µm to 2.3 µm for sintered samples at 1600°C. The strength was affected with Y2O3 content and no relevant influence of the Fe2O3 on density, microstructure or mechanical properties. Visible reflectance spectroscopy analyses, related to the CIELab scale, indicate variation in the contrast ratio as function of thickness of samples and coloring agent Fe2O3 content.